Structure and floristic list of a range in Guadalupe Cuautepec, Oaxaca - Matus-Santos, Elvia Itzel; Lozano-Trejo, Salvador; Hernández-Bautista, Jorge; Castañeda-Hidalgo, Ernesto; Santiago-Martínez, Gisela Margarita; Villegas-Aparicio, Yuri (Revista Mexicana de Ciencias Agrícolas, 2022)
In the last three decades, the plant formations of our country have faced a dynamic change of land use due to deforestation for livestock and agricultural activities. The research was developed during 2018 with the aim of determining the plant structure and identifying the forage species that develop and grow under adverse climatic conditions in a range of Guadalupe Cuautepec, Mixteca region, Oaxaca, Mexico. A stratified sampling of vegetation was performed at four sampling sites with three repetitions, including the herbaceous-graminoid, shrub and tree strata. The number of grasses per quadrant was determined and the identified species were recorded. The variables measured in the shrub and tree strata were basal diameter, crown area and total height. Four class ranges per variable were differentiated and an independence test with χ2 and a cluster analysis between variables were applied to know their affinity. Twenty-one species located in 19 genera belonging to 18 families, and 10 unidentified species were identified. The family Convolvulaceae was the most diverse and the genus Ipomoea was the most representative at the sampling sites. The range had a wide diversity of the genus Murucoides, characteristic of the cultural landscapes of the Mexican dry tropics. Of the individuals sampled, 94% were found with a height of less than 3.05 m, which confirms the vast presence of grass, herbaceous and shrub species, which reflects the lack of tree-shrub cover, of an undisturbed low deciduous rainforest.